2016
DOI: 10.1007/s00115-016-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Ambulante fachärztliche Versorgung psychischer Störungen

Abstract: The regional inequality of physician and psychotherapist density cannot be explained by regional differences in treatment needs. The results indicate potential improvements in healthcare provision for mental disorders in Germany through the adaptation to actual morbidity rates; however, the definition of treatment needs in mental disorders requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
1
3
0
4
Order By: Relevance
“…The extent to which this is reflected in care outcomes, such as more frequent drug therapy, more frequent inpatient admission or increased relapse, is a topic for future research. In any case, these findings – which are consistent with previous studies – militate against the hypothesis of a supplier-induced demand of psychotherapeutic and psychiatric care [ 19 ]. In well-supplied regions, utilization increases among people with current depressive symptoms; without these symptoms, it remains at a comparatively low level, despite the better levels of care provision.…”
Section: Discussionsupporting
confidence: 87%
“…The extent to which this is reflected in care outcomes, such as more frequent drug therapy, more frequent inpatient admission or increased relapse, is a topic for future research. In any case, these findings – which are consistent with previous studies – militate against the hypothesis of a supplier-induced demand of psychotherapeutic and psychiatric care [ 19 ]. In well-supplied regions, utilization increases among people with current depressive symptoms; without these symptoms, it remains at a comparatively low level, despite the better levels of care provision.…”
Section: Discussionsupporting
confidence: 87%
“…In Germany, only 34.6% of participants with 12-month MDD reported any service use due to mental health problems in 2009–2012 [65]. Locally varying access to mental health care has previously been identified as an important determinant of help-seeking behavior [66, 67]. In addition, increasing acceptance of mental health care services [55] and rising public knowledge appear to not have resulted in improved social acceptance of people with mental illness over time [54].…”
Section: Discussionmentioning
confidence: 99%
“…Data collected between 2009 and 2012 within a comprehensive study in Germany revealed a median delay between the appearance of the illness and evidence-based treatment of six to seven years among individuals who did not make treatment contact in the first year [ 6 ]. Possible reasons are fear of stigmatization [ 10 ], long waiting periods for outpatient psychotherapy [ 11 ], regional differences in availability [ 12 , 13 ] or problems with referrals for psychotherapy treatment. Possible difficulties are the non-detection of the mental disorder or a lack of knowledge of additional health care options [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%